MEMBANGUN ORGANIZATIONAL AGILITY PADA LAM TEKNIK DALAM MENGHADAPI DINAMIKA PEST, SN DIKTI, DAN STANDAR INTERNASIONAL - Raden Danny Pranayudha (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
The Independent Accreditation Institute for Engineering Study Programs (LAM Teknik) operates in a highly dynamic environment, characterized by changes in national regulations (SN Dikti, Permendiktisaintek No. 39 of 2025) and global pressures (Washington Accord standards, etc.). This study analyzes strategies for building organizational agility to respond to these changes. Through a literature and qualitative study approach, it was found that organizational transformation requires a shift from mere administrative compliance to the development of purpose-based and skill-based capabilities. The discussion highlights the application of the